MIRERC 056/2025: The Prevalence and Factors Associated with Multi Drug Resistant E. Coli Causing Urinary Tract Infections Among Women in Nyambene Hospital and Meru Level Five Hospital, Kenya - CLEOPHAS MBOGO, KIMANTHI; Dr. Dorothy Kagendo Kithinji; Dr. Patrick Kinyua Kubai (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Abstract Urinary tract infections are major health challenges among women globally. Urinary tract infections affect more than 400 million people globally each year. According to WHO about 60% of adult women experience urinary tract infection in their lifetime. Globally the prevalence of multidrug resistant urinary tract infection is between 35% to 50% with the most infections caused by E.coli. The prevalence of multidrug resistant E.coli in the US is 7.1%. The prevalence of multidrug resistant E.coli in European countries is 12 to 30%. The prevalence of multidrug resistant E.coli in Uganda and Tanzania is above 50% while the prevalence in Kenya is around 30% among all the infected patients. The increase in the number of cases of drug resistant strains of bacteria has made it very challenging to manage patients with urinary tract infection. Using empirical treatments without checking antimicrobial sensitivity and misuse of antibiotics has increased the prevalence of drug resistant urinary tract infections. E. coli account for about 70% of all urinary tract infections among women making it the most important organism for study. The objectives of the study are determine the antibiotics susceptibility pattern, the prevalence of and the risk factors associated with drug resistant E.coli among female patients in Meru level 5 and Nyambene Hospital.The study will be done among 288 female patients seeking services at Meru level five hospital and in Nyambene sub county Hospital. The study will be done between the month of March 2025 and May 2025. Data collection will be done using purposive sampling method as only those with active urinary tract infection will be selected for the study. Samples of patients confirmed to be having active urinary tract infections will be subjected to culture in CLED and MacConkey Agars after which sensitivity test will be performed to determine the antibiotic susceptibility. Data analysis will be done using SPSS and presentation will be done using graphs and charts.